Respuesta :

Piinoy

Answer:

(6, -3)

Step-by-step explanation:

I will solve this system using elimination.

[tex][tex]\left \{ {{-x+2y=-12} \atop {2x+3y=3}} \right.[/tex][/tex]

I will multiply [tex]-x+2y=-12[/tex] by 2 so that -x becomes -2x.

2(-x + 2y = -12)

Distribute.

-2x + 4y = -24

Now subtract this from the other equation.

2x + 3y = 3

-2x + 4y = -24

        7y  =  -21

Divide both sides by 7.

y = -3

Now that we have the value of y, plug it into the original equation.

-x + 2(-3) = -12

Simplify.

-x - 6 = -12

Add 6 to both sides.

-x = -6

Divide both sides by -1.

x = 6

(6, -3)

ACCESS MORE